2023
DOI: 10.3390/mca28020041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adhesive Materials in Re-Attachment of Crown and Crown–Root Fractures of Permanent Maxillary Anterior Tooth: A Computational Study

Abstract: Traumatic dental injuries (TDI) are frequent among individuals of all ages, with a prevalence ranging from 12–22%, with crown and crown–root fractures being the most common. Fragment reattachment using light-cured nanocomposites is the recommended method for the management of these fractures. Though there are several clinical studies that have assessed the efficacy of such materials, an in-silico characterization of the effects of traumatic forces on the re-attached fragments has never been performed. Hence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Due to the prevalence of frontal and incisal injuries [45], traumatic load was applied in the study. Since the maxilla are encased in skull, the upper surface of maxilla was constrained in all degrees of freedom A load of 10 MPa was applied to the natural crown of the central incisor and the porcelain crown of the implant to simulate the effects of a traumatic load, in line with previous literature [4]. Figure 4 shows the amount and location of pressure and constraint being applied that were used in this study.…”
Section: Loads and Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the prevalence of frontal and incisal injuries [45], traumatic load was applied in the study. Since the maxilla are encased in skull, the upper surface of maxilla was constrained in all degrees of freedom A load of 10 MPa was applied to the natural crown of the central incisor and the porcelain crown of the implant to simulate the effects of a traumatic load, in line with previous literature [4]. Figure 4 shows the amount and location of pressure and constraint being applied that were used in this study.…”
Section: Loads and Constraintsmentioning
confidence: 99%
“…Finite element analysis using patient based models have been able to address this aspect in past. Recently, Garg et al [4], performed the computational analysis of reattachment of fractured tooth using adhesive material (flowable composite, resin cement, and resin adhesive) on realistic tooth model. In their study they simulated the re-attachment of the fractured incisor tooth by using different composite based adhesive materials and measured the stress under different loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pusman et al state that the intermediate material and the bonding adhesive have an impact on the reattached tooth’s fracture strength [ 2 ]. Garg et al found that a flowable composite shows better results than resin cement in fracture reattachment [ 38 ].…”
Section: Reviewmentioning
confidence: 99%